Virtual Sound: Examining Glitch and Production. - Vanhanen, Janne (Contemporary Music Review, 2003)
The arrival of so-called laptop music in the late 1990s also created a distinctively new aesthetic, which utilized the errors and disturbances taking place in digital sound processing. This focus on the glitch became an emblematic sound and signaled a new approach to the relation between the sound artist and the tools of music production by focusing on the production process itself. There has been a steady increase in the quantity of music produced under the concept of glitch, and its "aesthetics of failure" has lost much of its avant-garde status by becoming a part of an established musical vocabulary. I wish to consider the laptop producer's role, which overlaps academia and popular culture, by offering further analysis on the concept of glitch and the production process and will conclude that the laptop artist inhabits a paradoxical position, both culturally (academia/pop) and aesthetically (artistry/machinic production).